Penerapan Role Playinng pada Pembelajaran Matematika di Sekolah Dasar - Rindi Dwi Ramadhani Saragih; Rohana Silaen; Hendry Meiman; Melvin Lombu; Taruli Marito Silalahi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The following article has the following objectives: (1) to understand the meaning of role playing (2) the purpose of implementing role playing (3) the function and provisions in implementing the role playing model for elementary school students (4) the advantages and disadvantages of using role playing. In implementing role playing, there are quite good benefits for training and increasing creativity and understanding students' learning and mathematical concepts, especially at the elementary level. At that age, a strong understanding is needed because they are not yet able to think abstractly. Therefore, a method is needed that emphasizes the concept so that it is easier for students to learn mathematics. It is also necessary to make more efforts to emphasize understanding the concept so that students have a good enough basis for thinking to achieve other cognitive abilities.